Peningkatan Literasi Ibu Rumah Tangga sebagai Upaya Mitigasi Risiko Penggunaan Gawai - Adhani, Lisa; Aliyah, Andi Nur; Kusumawati, Amora; Afifah, Muanda; Kartika, Wahyu; Setiawati, Siti (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
This Community Service (PKM) is conducted through counselling in the densely populated ​​Peninggaran Barat sub-district, Kebayoran Lama, South Jakarta. The purpose of this PKM is to provide input that is expected to be a solution to the concerns of mothers regarding dependence on gadgets that are detrimental to their environment in general, and children in particular, especially early childhood. Currently, dependence on gadgets is something that cannot be avoided, coupled with the rapid development of digital and information technology. From these changes, mothers are the ones who feel the impact the most. Mothers are required to be able to accompany their children in learning and synergize with teachers at school, especially for early childhood. This PKM uses the constructivism paradigm method, namely delivering material and discussions about the importance of literacy and implementing a culture of literacy through counseling The results of the PKM show that mothers are increasingly aware of the importance of literacy so that they can comfortably accompany their children to learn , use gadgets intelligently, and can provide solutions to conflicts that occur with their environment.